The Effect of Competence, Facilities, Discipline And Leadership on The Performance of Health Workers at The Wedi Community Health Center, Klaten - Wahyu Ciptadi; Istiatin Istiatin; Yunus Yunus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of health worker performance on competence, facilities, work discipline, leadership using descriptive quantitative methods. The quantitative data of this study are in the form of respondents' opinions in the form of questionnaires. The location chosen as the research location is the Wedi Community Health Center environment, Klaten Regency. The time for this study is adjusted to the achievement of data and information needed by researchers, estimated to be 5 months from July - November 2025. The population of this study is all health workers in the Wedi Community Health Center Environment, both State Civil Apparatus (ASN) and Non-ASN, totaling 41 people. The sample used in the study is a saturated sample where all 41 people are sampled. The sampling technique used in this study is a census technique or saturated sample. After the data was collected, an analysis was carried out by processing the research data using multiple linear regression analysis tools with the help of SPSS 25 software. Hypothesis testing results indicate that competence, facilities, and leadership have a positive and significant effect on healthcare worker performance, while discipline has a negative but significant effect.